Изучение активности каталазы в онтогенезе тутового шелкопряда при действии электростатического поля - Барабанова, В.В.; Колыбин, В.А. (Вестник зоологии, 1968)
The effect is studied of an electrostatic field with voltage of 250 and 600V on the catalase activity of Bombyx mori L. It is shown that the enzyme activity is suppressed at first and then under the durable influence of the field the insects, apparently, get accustomed to its effect and the catalase activity is normalized. The influence of the field after-effect is also observed. Change in catalase activity under the effect of the electric field confirms a hypothesis on the possible action of aeroionization on a living organism by means of iron-containing enzymes.